2018
DOI: 10.1109/twc.2018.2868096
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Framework of Hybrid Beamforming in Multi-Cell Millimeter-Wave Systems

Abstract: Multi-cell wireless systems usually encounter both intracell and inter-cell interference, which can be mitigated via coordinated multipoint (CoMP) transmission. Previous works on multi-cell analysis in the microwave band generally consider fully digital beamforming, requiring a complete radio-frequency chain behind each antenna. This is practically infeasible for millimeter-wave (mmWave) systems where large amounts of antennas are necessary to provide sufficient gain and to enable transmission/reception of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…For the vehicle antenna configuration modeling, given the fast movement of vehicles and the balance between the cost and the system complexity [31], in this work, we adopt a hybrid beamforming model [32], [33]. Note that mmWaves and hybrid beamforming promise to be widely used in the coming V2X networks, particularly in the era of 5G [28] (even 6G [34]).…”
Section: B Assumption and System Modelmentioning
confidence: 99%
“…For the vehicle antenna configuration modeling, given the fast movement of vehicles and the balance between the cost and the system complexity [31], in this work, we adopt a hybrid beamforming model [32], [33]. Note that mmWaves and hybrid beamforming promise to be widely used in the coming V2X networks, particularly in the era of 5G [28] (even 6G [34]).…”
Section: B Assumption and System Modelmentioning
confidence: 99%
“…It is shown that a joint transmitter-receiver HBF design problem is usually difficult to deal with [8,17]. Therefore, researchers usually focus on the two-step HBF design algorithm [8,18,19]. Most two-step HBF design algorithms need to assume the analog matrix F RF is fixed to find the optimal digital matrix F BB .…”
Section: F-hbf Algorithmmentioning
confidence: 99%
“…In various types of systems presented, fixed multiple beams and fully adaptive smart antennas are commonly used. With the assistance of the smart antenna system, a beamforming can be developed to reduce the bit error rate and increased the capacity in the wireless communication system …”
Section: Introductionmentioning
confidence: 99%
“…A classic example is the performance versus price, where the designer is forced to trade off one desired objective for another. The traditional approach to this problem is to combine the objectives into a single cost function using a weighted sum . For multiobjective problems in UWB communication, a smart UWB circular array at the transmitter is proposed in Chien et al However, the receiver with only one antenna is used in Chien et al, and the multiobjective functions are optimized by the genetic algorithm and asynchronous particle swarm optimization (APSO).…”
Section: Introductionmentioning
confidence: 99%